A Mobile Usability Evaluation of a Pregnancy App - Hussain, Azham; Mkpojiogu, Emmanuel O. C.; Fadzil, Najdawati; Hassan, Norhasizasuriati; Zaaba, Zarul Fitri (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The upsurge in the use of mobile devices worldwide has led to an increasing number of mobile apps developed and available in the market today. This makes the mobile usability of these apps an important issue to consider. This study evaluates the mobile usability of Amila Pregnancy app, a mobile assistive app for pregnant women and expectant mothers. The paper reports on the outcome of a mobile usability evaluation for Amila Pregnancy app. In the study, five usability qualities were evaluated in line with the Jakob Nielsen’s usability principles, these are, inter alia: effectiveness, efficiency, learnability, memorability and satisfaction. The outcome shows the trouble mobile users had in understanding displayed icon, locating the information provided, re-finding it and in navigating through the mobile app. In conclusion, the study recommends that the main menu of the app be further improved upon to boost its usability.